2010
DOI: 10.1016/j.cell.2010.05.017
|View full text |Cite
|
Sign up to set email alerts
|

A MicroRNA Targeting Dicer for Metastasis Control

Abstract: Although specific microRNAs (miRNAs) can be upregulated in cancer, global miRNA downregulation is a common trait of human malignancies. The mechanisms of this phenomenon and the advantages it affords remain poorly understood. Here we identify a microRNA family, miR-103/107, that attenuates miRNA biosynthesis by targeting Dicer, a key component of the miRNA processing machinery. In human breast cancer, high levels of miR-103/107 are associated with metastasis and poor outcome. Functionally, miR-103/107 confer m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
506
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 605 publications
(548 citation statements)
references
References 46 publications
(48 reference statements)
37
506
2
3
Order By: Relevance
“…13,14 This is supported by a recent report, in which DICER was shown to be specifically targeted by the miR-103/107 family in breast cancer, where overexpression of miR-103/107 members induced epithelial-to-mesenchymal transition via reduced levels of miR-200b. 31 Therefore, direct regulation of DICER1 levels by miR-9 overexpression could contribute to transformation and invasiveness in HL.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 This is supported by a recent report, in which DICER was shown to be specifically targeted by the miR-103/107 family in breast cancer, where overexpression of miR-103/107 members induced epithelial-to-mesenchymal transition via reduced levels of miR-200b. 31 Therefore, direct regulation of DICER1 levels by miR-9 overexpression could contribute to transformation and invasiveness in HL.…”
Section: Discussionmentioning
confidence: 99%
“…129 At the cellular level, one of the key events associated with miR-103/107 is the induction of EMT via the downregulation of miR-200 expression. 130 Song et al found that miR-22 triggered EMT, enhanced invasiveness, and promoted metastasis in mouse xenografts. They also demonstrated that miR-22 induced metastatic potential by silencing miR-200 through the targeting of ten-eleven translocation proteins, which are a family of methylcytosine dioxygenases.…”
Section: Mirna In Triple-negative Breast Cancermentioning
confidence: 99%
“…It often involves transforming growth factor (TGF)-b and SMAD (Derynck and Akhurst, 2007). EMT cells are presumed to be responsible for metastasis (Leroy et al, 1994;Christiansen and Rajasekaran, 2006;Alexander et al, 2008;Giampieri et al, 2009;Martello et al, 2010;Pantel and Alix-Panabieres, 2010). Here are some recent arguments for this statement.…”
Section: Epithelial-to-mesenchymal Transitionmentioning
confidence: 99%